2018
DOI: 10.1557/mre.2018.2
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and opportunities at the nexus of energy, water, and food: A perspective from the southwest United States

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 135 publications
(291 reference statements)
0
15
0
Order By: Relevance
“…In the meantime, the energy-water-nexus literature has come up with individual technologies, policy recommendations and system analysis techniques to study both the electricity and water supply systems. Policy-based studies tend to take a qualitative and sometimes statistical approach while focusing on a specific geographical region [3,8,24,[41][42][43][44][45][46][47][48][49][50][51][52]. Similarly, system analysis techniques have been case-study driven, geography-specific, rather than generic methodologies that are generally applicable.…”
Section: Literature Gapmentioning
confidence: 99%
See 2 more Smart Citations
“…In the meantime, the energy-water-nexus literature has come up with individual technologies, policy recommendations and system analysis techniques to study both the electricity and water supply systems. Policy-based studies tend to take a qualitative and sometimes statistical approach while focusing on a specific geographical region [3,8,24,[41][42][43][44][45][46][47][48][49][50][51][52]. Similarly, system analysis techniques have been case-study driven, geography-specific, rather than generic methodologies that are generally applicable.…”
Section: Literature Gapmentioning
confidence: 99%
“…To illustrate, a recent study estimates that water withdrawals by electricity generating facilities in 2010 constituted 45% of the overall freshwater withdrawals in the United States with approximately 2% of that water being consumed as a result [4]. In addition to cooling purposes, large quantities of water are utilized in the extraction of raw fuels for electricity generation [7,8]. A recent study reported that the water consumption (in liters per gigajoule -L/GJ) for worldwide production of carbon-based and nuclear fuels is as follows: 1) traditional oil (3-7 L/GJ); 2) oil from oil sands (70-1800 L/GJ); 3) conventional natural gas (minimal water use); 4) shale gas (36-54 L/GJ); 5) coal (5-70 L/GJ); and 6) uranium (4-22 L/GJ) [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, better management of fuel intensive resources and end user consumption behaviours can alleviate the strain on these commodities [30]. Therefore, flexible control of the energy supply and use system [19,31] is crucial within the context of renewable energy and storage integration [32]. In addition, a recent study shows the water usage for carbon-based and nuclear fuel-based energy as follows: (i) oil from oil reservoirs (70-1800 L/GJ), (ii) shale gas (36-54 L/GJ), coal (5-70 L/GJ), (iii) uranium (4-22 L/GJ), and (iv) traditional oil (3-7 L/GJ) [31].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, flexible control of the energy supply and use system [19,31] is crucial within the context of renewable energy and storage integration [32]. In addition, a recent study shows the water usage for carbon-based and nuclear fuel-based energy as follows: (i) oil from oil reservoirs (70-1800 L/GJ), (ii) shale gas (36-54 L/GJ), coal (5-70 L/GJ), (iii) uranium (4-22 L/GJ), and (iv) traditional oil (3-7 L/GJ) [31]. Another study reveals that 76.9% of electricity is produced from oil, natural gas, coal, and nuclear fuels in the year 2015, while only 16% is generated from hydrothermal power plants.…”
Section: Introductionmentioning
confidence: 99%